2017
DOI: 10.1002/slct.201700577
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Base‐Solvent Controlled Chemoselective Azide Attack on an Ester Group versus Keto in Alkyl 3‐Substituted 3‐Oxopropanoates: Mechanistic Insights

Abstract: During the exploration of arylazides reactions with alkyl 3‐substituted‐3‐oxopropanoates under the Dimroth reaction conditions (MeONa‐MeOH) azide attack on ester group versus keto was found out in few examples yielding stable 3‐alkyl‐2‐diazo‐3‐oxo‐N‐(aryl)propanamides instead of obvious target 1‐aryl‐5‐alkyl‐1H‐1,2,3‐triazole‐4‐carboxylic acids. The formation of diazocompounds was observed in case of 3‐(4,4‐diethoxymethyl)‐, isopropyl‐, cyclopropyl‐3‐oxopropanoate in the reaction with arylazides, especially, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
1
8
0
2
Order By: Relevance
“…1, the 4-methoxyphenyl and 1,2,3-triazole rings are turned relative to each other by 87.77 (7) because of a significant steric hindrance of the cyclopropyl ring relative to the 4-methoxyphenyl substituent [the N1-C9-C11-C13 and N1-C9-C11-C12 torsion angles are 41.2 (4) and À31.6 (4) , respectively]. The above angle between the planes is comparable with that for the bulky 5-(2-phenylhydrazineylidene)methyl analogue [73.3 (2) ; Pokhodylo et al, 2018] but is considerably larger than in the structure of 5-cyclopropyl-1-(3-methoxyphenyl)-1H-1,2,3triazole-4-carboxylic acid [39.1 (2) ] in which the cyclopropyl ring is oriented to the triazole ring (Pokhodylo et al, 2017) or in 5-methyl-1-(4-nitrophenyl)-1H-1,2,3-triazol-4-ylphosphon-ate [45.36 (6) ; Pokhodylo et al, 2020]. In selected 5-free triazoles, 1-(3-bromo-or 4-fluorophenyl)-1H-1,2,3-triazol-4yl)methyl methylphosphonates, this angle is 22.9 (3) and 15.7 (2) , respectively (Pokhodylo, Shyyka et al, 2019).…”
Section: Structural Commentarymentioning
confidence: 65%
See 1 more Smart Citation
“…1, the 4-methoxyphenyl and 1,2,3-triazole rings are turned relative to each other by 87.77 (7) because of a significant steric hindrance of the cyclopropyl ring relative to the 4-methoxyphenyl substituent [the N1-C9-C11-C13 and N1-C9-C11-C12 torsion angles are 41.2 (4) and À31.6 (4) , respectively]. The above angle between the planes is comparable with that for the bulky 5-(2-phenylhydrazineylidene)methyl analogue [73.3 (2) ; Pokhodylo et al, 2018] but is considerably larger than in the structure of 5-cyclopropyl-1-(3-methoxyphenyl)-1H-1,2,3triazole-4-carboxylic acid [39.1 (2) ] in which the cyclopropyl ring is oriented to the triazole ring (Pokhodylo et al, 2017) or in 5-methyl-1-(4-nitrophenyl)-1H-1,2,3-triazol-4-ylphosphon-ate [45.36 (6) ; Pokhodylo et al, 2020]. In selected 5-free triazoles, 1-(3-bromo-or 4-fluorophenyl)-1H-1,2,3-triazol-4yl)methyl methylphosphonates, this angle is 22.9 (3) and 15.7 (2) , respectively (Pokhodylo, Shyyka et al, 2019).…”
Section: Structural Commentarymentioning
confidence: 65%
“…In addition to the antitumor studies, 1H-1,2,3-triazole-4-carboxamides exhibit other biological activities such as fungicidal (Wang et al, 2014), antiviral (Krajczyk et al, 2014) and antimicrobial (Jadhav et al, 2017) activities and were found to be inhibitors of the Wnt/catenin signalling pathway (Obianom et al, 2019). It should be noted that the diversity of such compounds can be obtained by amidation of 1H-1,2,3-triazole-4-carboxylic acids prepared by convenient Dimroth synthesis and further modifications (Pokhodylo et al, 2009(Pokhodylo et al, , 2017(Pokhodylo et al, , 2018Pokhodylo, Savka et al, 2010;. Given the considerable interest in such scaffolds for drug discovery, a detailed study of their structural features is relevant and the crystal structure of the title compound, C 19 H 17 ClN 4 O 2 , is described herein.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Recently, we reported that K 2 CO 3 /DMSO is a mild base‐solvent system which provides high selectivity in the reaction of azides with α ‐ketomethylenic compounds and eliminates undesired concurrent processes. Therefore, we adopted K 2 CO 3 in DMSO to test a number of arylazides with diverse substituents.…”
Section: Resultsmentioning
confidence: 99%
“…Реакції ацилювання 1,1-дихлоретилену хлорангідридами кислот за типом реакції Фріделя-Крафтса є зручним шляхом синтезу β-трихлорометилкетонів та їх похідних -дихлоровінілкетонів. Такі β-хлорокетони є попередниками широковживаних в органічному синтезі біфункціональних реагентів, зокрема, β-кетоестерів [1], β-кетоортоестерів [2,3] та різноманітних гетероциклічних сполук, таких як хлоропіразоли [4][5][6][7], піримідини [8,9], 1,3-оксазини [10], 1,3-тіазини [11,12], бензо-l,3-тіоли [13] тощо. В тактиці органічного синтезу β-хлорокетони розглядають як синтетичні еквіваленти діелектрофільного синтону + С-С-С + і можуть бути використані для введення в молекулу фрагмента =С-С=C-Cl.…”
Section: вступunclassified